(untitled) (International Journal of Management and Sustainability, 2018)
The major purpose of this study was to investigate the relationship between sport organizational management practices and coaching leadership style of Ethiopian primer league football clubs. To this end descriptive survey method were employed. The data collected by two Questionnaires the first one from sport organizational management practices and the second one Leadership Scale for Sport (LSS) from selected football club players. Assess the validity and reliability of the questionnaires by areas of professional expertise. The target population of this study were all 14 Ethiopian primer league football club players. Based on Ethiopian football federation rules and regulations 25 players registered for one year computation 25x14(N=350).The researcher selected only 4(28.57%) top two and bottom tow clubs from 2015/2016 computation year by using purposive sampling techniques. The total number of participants in this study was 4x25(N=100). The research approach applied for this study were quantitative approach in nature. The Statistical Package for Social Science (SPSS) version 20 used for data analysis Depending on the nature of the basic questions, appropriate statistical techniques such as mean, standard deviation, ANOVA (analysis of variance) ,and Pearson correlation were used for data analysis. The level of significance is set at 0.05. The researcher assumption/hypothesis was: - There is no significant difference in sport organizational management practices, Perceive and Prefer of coaching leadership behaviour of player’s indices in Ethiopian premier league football clubs. The study findings indicated that, there is significant difference between clubs and sport organizational management practice, there is significant difference between clubs and perceive coaching leadership style and there is no significant difference between clubs and prefer coaching leadership style. Finally there was positive relationship in sport organizational management practice, perceive and prefer of coaching leadership behaviour.